2012
DOI: 10.1124/mol.112.082958
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate Receptor 1 (S1P1) Upregulation and Amelioration of Experimental Autoimmune Encephalomyelitis by an S1P1 Antagonist

Abstract: Sphingosine 1-phosphate receptor 1 (S1P 1 ) is a G proteincoupled receptor that is critical for proper lymphocyte development and recirculation. Agonists to S1P 1 are currently in use clinically for the treatment of multiple sclerosis, and these drugs may act on both S1P 1 expressed on lymphocytes and S1P 1 expressed within the central nervous system. Agonists to S1P 1 and deficiency in S1P 1 both cause lymphocyte sequestration in the lymph nodes. In the present study, we show that S1P 1 antagonism induces lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…RP-001 treatment also induced reduction of endothelial S1PR 1 -eGFP expression levels. Such agonistdependent changes in endothelial expression levels of GFPtagged S1PR 1 have been previously reported (6) and were confirmed by flow cytometry and Western blot analysis (5,6,18).…”
Section: Discussionsupporting
confidence: 49%
“…RP-001 treatment also induced reduction of endothelial S1PR 1 -eGFP expression levels. Such agonistdependent changes in endothelial expression levels of GFPtagged S1PR 1 have been previously reported (6) and were confirmed by flow cytometry and Western blot analysis (5,6,18).…”
Section: Discussionsupporting
confidence: 49%
“…1 E-G). The inability of a neutral S1PR1 antagonist to inhibit IFN-α amplification was confirmed in human pDCs using the potent and selective Ex26 S1PR1 antagonist (13) (Fig. 1E and Table 1).…”
Section: Significancementioning
confidence: 93%
“…Codocking of S1P and CYM-5541 suggested that the receptor pocket could spatially expand in the lower region of the hydrophobic pocket to accommodate CYM-5541 in addition to S1P. In the presence of S1P, the pocket opens up in the lower hydrophobic region adjusting CYM-5541 is demonstrated to be especially prolonged Mullershausen et al 2009;Cahalan et al 2013), the differences between S1P and other ligands either reflect a conformational change in receptor (for which no strong evidence has yet been shown) or a difference in the stability of the signaling complex between S1P and FTY-phosphate. A relatively faster off-rate for S1P may be sufficient to alter the duration of the endosomal signaling complex and the recruitment of beta-arrestin and an E3 ligase (Oo et al 2011).…”
Section: Sphingosine 1-phosphate: a Signaling Lysophospholipidmentioning
confidence: 94%
“…Study of S1P receptors in these models has given insights into receptor expression across and within tissues, and the malleability of receptor modulation by ligand in vivo, and how that may differ in tissue specific ways (Teijaro et al 2011;Cahalan et al 2011;Gonzalez-Cabrera et al 2012;Cahalan et al 2013;Sarkisyan et al 2012). …”
Section: Sphingosine 1-phosphate: a Signaling Lysophospholipidmentioning
confidence: 98%
See 1 more Smart Citation